Utilization of empty fruit bunch derived vapor for carbon deposition within iron ores - Marzuki, Hasan; Rozhan, Alya Naili; Hadi, Purwanto (Trans Tech Publications Ltd, Switzerland, 2022)
Metallurgical coke is the main source of fuel and reducing agent for iron and steel industry. Empty fruit bunch (EFB) biomass which is abundantly available in Malaysia could be utilized as a source of energy as well as reducing agent in iron making process. This research presents carbon infiltration within low-grade iron ore via chemical vapor infiltration (CVI) method from EFB pyrolysis vapor. Low-grade iron ore was first heated to remove the combined water (CW) that consequently created pore network within the iron ore. These pores would act as sites for carbon infiltration in the iron ore. The EFB treatment on iron ore has been carried out at different temperatures and the effect of pyrolysis temperature on the carbon infiltration has been investigated. The Brunauer−Emmet−Teller (BET) and Barrett−Joyner−Halenda (BJH) methods have been performed to analyze pore surface and pore volumes of the iron ore. Pore surface and pore volume decreased as the temperature increased indicated that more carbon has been deposited. Using X-ray diffraction (XRD) analysis, it was shown that the low-grade iron ore has been transformed into iron (Fe). The infiltrated carbon from the EFB pyrolysis vapor in the pore surface iron ore is proven to be able to be utilized as source of energy and reducing agent to partially replace metallurgical coke in the blast furnace in order to reduce emission of harmful gas.